Scarless platysmaplasty for platysmal bands - Shiffman, Melvin A.; Mirrafati, Sid (Indian Journal of Plastic Surgery, 2004)
Transection of plastysmal bands has required a surgical approach that leaves scars and limits patient activities for a period of time. The author has developed a sirnple method to transect the platysmal bands under local anesthesia without resorting to skin incisions. The transection is performed with the use of a Vicryl® suture that is inserted through the skin, around the platysmal band, and then out thiOugh the original entry pOint. A back and forih motion of the suture cuts through the band.